Transcriptional and post-transcriptional regulation of the Escherichia coli luxS mRNA; involvement of the sRNA MicA. - Klas I Udekwu (Public Library of Science (PLoS), 2010)
Background The small RNA (sRNA) MicA has been shown to post-transcriptionally regulate translation of the outer membrane protein A (OmpA) in Escherichia coli. It uses an antisense mechanism to down-regulate OmpA protein synthesis and induce mRNA degradation. MicA is genomically localized between the coding regions of the gshA and luxS genes and is divergently transcribed from its neighbours. Transcription of the luxS gene which originates within or upstream of the MicA sequence would thus be complementary to the sRNA. LuxS regulation is as yet unclear. Methodology/principal findings In this report, I show that the luxS mRNA exists as three long (major) transcripts of sizes that suggest just such interaction. The sRNA MicA's expression affects the abundance of each of these luxS transcripts. The involvement of the ribonuclease, RNase III in the accumulation of the shortest transcript is demonstrated. When MicA accumulates during growth, or is induced to be over-expressed, the cleaved mRNA species is observed to increase in intensity. Using primer extension and 5'-RACE experiments in combination with sRNA overexpression plasmids, I identify the exact origin of two of the three luxS transcripts, one of which is seen to result from a previously unidentified σ(S) dependent promoter. Conclusions/significance The presented data provides strong evidence that MicA functions in cis and in trans, targeting both luxS mRNA as well as the previously established ompA and phoP regulation. The proposed luxS regulation by MicA would be in tandem with another sRNA CyaR, shown recently to be involved in inhibiting translation of the luxS mRNA. Regulation of luxS expression is additionally shown to occur on a transcriptional level via σ(S) with variable transcript levels in different growth phases unlike what was previously assumed. This is the first known case of an sRNA in E. coli which targets both in cis (luxS mRNA) and in trans (ompA and phoP mRNAs).